Enhancing EFL Vietnamese Students’ Communicative Competence through Selected Speaking Strategies - Huu Chanh, Nguyen (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
In Vietnamese tertiary education, there is a growing focus on enhancing students' speaking skills through the use of speaking strategies. This study aims to investigate the effectiveness of different types of speaking strategies when employed in authentic settings. A mixed-methods research approach was employed, using a questionnaire and interview to collect data from 90 pre-intermediate undergraduate students at a local university. Random sampling was utilized with the support of SPSS version 20. Ten strategies were carefully designed to meet the requirements of tasks in the pre-, while-, and post-speaking phases, based on previous studies. The results showed that the use of these speaking strategies had a positive impact on EFL students' communicative competence, as evidenced by their scores and feedback. Moreover, teachers were found to be able to vary their speaking strategies according to the specific types of activities, with a particular strategy being implemented in a given class meeting. This research represents one of the first empirical studies investigating the roles of speaking strategies in improving students' communication skills and achieving learning autonomy in the Vietnamese tertiary education context. Furthermore, it is hoped that the findings will make significant contributions to the curriculum development of programs and to Target No.4: Quality Education, as defined by the United Nations, both in Vietnam and globally. Overall, this study highlights the importance of effective speaking strategies in EFL education and provides valuable insights for educators seeking to enhance their students' communicative competence.